Analisis LC-MS/MS Senyawa Metabolite Ekstrak Etanol daun Miana (Coleus scutellariodes (L) Benth) dan Potensinya sebagai Kandidat Obat Alzheimer - Julius Alvin Novensius Sinurat; Catherine Putri Bulan; Veronika Vitadella; Madyawati Latief; Indra Lasmana Tarigan (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2024)
A secondary metabolic compound in plants is a bioactive substance connected to the chemical content of the plant, so some can be used as a medicine. Miana (Coleus Scutellariodes (L) Snapped) is a medicinal plant that has a potentially potent bioactive compound as an anticancer. Extraction of miana leaf with ethanol solvents held by an analysis of lc-ms, which shows some metabolite compounds contained in the miana. The method used is the extraction of miana leaves with ethanol, the study of compounds obtained from lc-ms, for the compound screening using Pchembl and ChemSpider websites and Pchembl's web server. The purpose of this research is to know and predict the potential of the associated bioactivity of the compounds found as candidates for new drugs. The results derived from this study are metabolite compounds found in the miana that are potentially Alzheimer drugs based on the screening done using Pchembl webservers based on a target protein acquired from extracting is acetylcholinesterase, which contains acetylcholinesterase as the target molecule that ACTS as an Alzheimer drug